Interactions between Mycoplasma pulmonis and immune systems in the mealworm beetle, Tenebrio molitor. (November 2019) - Lim, Sooa; Yun, Hwa-Kyung; Kang, Ki Mo; Lee, Bok Luel; Won, Ran; Lee, In Hee
Abstract: Mycoplasmas, the smallest self-replicating organisms, are unique in that they lack cell walls but possess distinctive plasma membranes containing sterol acquired from their growth environment. Although mycoplasmas are known to be successful pathogens in a wide range of animal hosts, including humans, the molecular basis for their virulence and interaction with the host immune systems remains largely unknown. This study was conducted to elucidate the biochemical relationship between mycoplasma and the insect immune system. We investigated defense reactions of Tenebrio molitor that were activated in response to infection with Mycoplasma pulmonis . The results revealed that T. molitor larvae were more resistant to mycoplasma infection than normal bacteria equipped with cell walls. Intruding M. pulmonis cells were effectively killed by toxins generated from activation of the proPO cascade in hemolymph, but not by cellular reactions or antimicrobial peptides. It was determined that these different anti-mycoplasma effects of T. molitor immune components were primarily attributable to surface molecules of M. pulmonis such as phospholipids occurring in the outer leaflet of the membrane lipid bilayer. While phosphatidylcholine, a phospholipid derived from the growth environment, contributed to the resistance of M. pulmonis against antimicrobial peptides produced by T. molitor, phosphatidylglycerol was responsible for triggering activation of the proPO cascade. Graphical abstract: Image 1 Highlights: We investigated the immune reactions of Tenebrio molitor against mycoplasma. T. molitor larvae were more resistant to mycoplasma infection than normal bacteria with cell wall. Intruding mycoplasma into the hemocoel was effectively killed by the prophenoloxidase system occurring in the hemolymph. Anti-mycoplasma activity of T. molitor was attributable to phospholipids occurring in the outer leaflet of mycoplasma membrane. Phosphatidylglycerol was responsible for triggering activation of the prophenoloxidase cascade in the hemolymph.